Process heat transfer : principles, applications and rules of thumb. - Serth, R. W.; Lestina, Thomas G. (Amsterdam : Academic Press is an imprint of Elsevier, 2014)
Process Heat Transfer is a reference on the design and implementation of industrial heat exchangers. It provides the background needed to understand and master the commercial software packages used by professional engineers in the design and analysis of heat exchangers. This book focuses on types of heat exchangers most widely used by industry: shell-and-tube exchangers (including condensers, reboilers and vaporizers), air-cooled heat exchangers and double-pipe (hairpin) exchangers. It provides a substantial introduction to the design of heat exchanger networks using pinch technology, the most efficient strategy used to achieve optimal recovery of heat in industrial processes.
Heat Conduction -- Convective and Radiative Heat Transfer -- Heat Exchangers -- Design of Double-Pipe Heat Exchangers -- Design of Shell and Tube Heat Exchangers -- The Delaware Method -- The Stream Analysis Method -- Heat Exchanger Networks -- Boiling Heat Transfer -- Reboilers -- Condensers -- Air-Cooled Heat Exchangers -- Appendix
engineering bookfair2015
Previous edition: published as by R.W. Serth, 2007.
First edition 2007.
Includes bibliographical references and index.
Keywords: Heat -- Transmission; Heat exchangers; Heat exchangers -- Design; Heat -- Transmission -- Computer programs